1995
DOI: 10.1128/jcm.33.7.1760-1764.1995
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Etest for susceptibility testing of rapidly growing mycobacteria

Abstract: MICs of amikacin, cefoxitin, ciprofloxacin, clarithromycin, doxycycline, and imipenem were determined by Etest for 100 clinical strains of rapidly growing mycobacteria and compared with MICs determined by a reference agar dilution method. Etest MICs were also determined by an alternative inoculum application (agar overlay) method and compared with MICs determined by the inoculum application method recommended by the manufacturer (swabbing). Agreement between Etest and agar dilution MICs within ؎1 log 2 dilutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 13 publications
1
19
1
Order By: Relevance
“…Drug susceptibility testing (DST), was performed on the M. abscessus subsp. abscessus isolate using the E-test (AB Biodisk, Solna, Sweden) and the broth microdilution methods, the former with both 4 day and 14 day readings (Sensititre, Trek Diagnostic Systems, USA) [20,21]. Results were evaluated according to the breakpoints reported in the CLSI document from 2011 (Table 2) [19].…”
Section: Case Reportmentioning
confidence: 99%
“…Drug susceptibility testing (DST), was performed on the M. abscessus subsp. abscessus isolate using the E-test (AB Biodisk, Solna, Sweden) and the broth microdilution methods, the former with both 4 day and 14 day readings (Sensititre, Trek Diagnostic Systems, USA) [20,21]. Results were evaluated according to the breakpoints reported in the CLSI document from 2011 (Table 2) [19].…”
Section: Case Reportmentioning
confidence: 99%
“…Etest (AB BIODISK, Solna, Sweden), an accurate MIC method, has emerged as the method of choice for the susceptibility testing of fastidious organisms (16), including rapidly growing mycobacteria (2,5,11). Preliminary results have shown that Etest is a promising new method for the susceptibility testing of more slowly growing mycobacteria as well (19).…”
mentioning
confidence: 99%
“…Susceptibility testing of clinically significant isolates of the rapidly growing mycobacteria is recommended because these organisms differ in susceptibility to the antimicrobial agents commonly used for therapy (2,4,(11)(12)(13)(14)(15)(16). Based on data from the Centers for Disease Control and Prevention, many laboratories in the United States do such testing by a variety of methods (21).…”
Section: Discussionmentioning
confidence: 99%
“…The problem with the existing cefoxitin breakpoints is that the resistance breakpoint (64 g/ml) is in the middle of the normal MIC range for untreated isolates of several of the rapidly growing mycobacteria. Previous studies have demonstrated that the cefoxitin MICs for more than 90% of isolates of M. fortuitum and M. abscessus range from 16 to 64 g/ml, with a mode of 32 g/ml (2,12,14). a For laboratories that infrequently isolate rapidly growing mycobacteria, sending isolates to an experienced reference laboratory is recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation